A case of dermatofibrosarcoma protuberans and reflectance confocal microscopy of a post‐surgical skin graft. Issue 2 (9th November 2021) - Nawrocki, Shiri; Rubin, Alexandra; Srivastava, Radhika; Chamorro, Paola; Rao, Babar K.; Wassef, Cindy M.
Abstract: Dermatofibrosarcoma protuberans (DFSP) is an overall rare malignancy yet is one of the most common cutaneous sarcomas. The diagnosis of DFSP is typically made following histopathologic examination of the lesion, classically revealing a storiform pattern of spindle cells with elongated nuclei infiltrating the dermis and subcutis. Surgical excision is the standard treatment. Local recurrence is estimated to occur in 20−50% of cases, thus frequent postsurgical monitoring is required. Noninvasive imaging modalities offer a potential alternative to multiple repeat biopsies. We report the first case where reflectance confocal microscopy accompanied clinical examination in monitoring for DFSP recurrence postsurgical excision.